2016
DOI: 10.20884/1.anprod.2016.18.1.540
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Papain Crude Extract Addition in Diets on Broilers Production Performances

Abstract: This study was conducted to evaluate the effects of papain crude extract addition in mash and pellet feed forms on production performance of broiler chickens in order to obtain the best level of extract papain in mash or pellet form. This natural protease enzyme was extracted from unripe papaya. A complete random design was applied in this study and it was arranged with factorial 4*2 and three replications. The treatments were 4 levels of papain (0, 0.03, 0.05, and 0.07 %) and two physical forms of feed (mash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similar to these previous studies, our findings showed that dietary supplementation of acid protease in corn-soybean meal-based diets linearly increased BWG and decreased the FCR during 18 to 35 days and overall. Rumokoy et al, (2016) also demonstrated that all treatment level (0.03, 0.05 and 0.07%) of papain crude extract (a proteolytic enzyme that can break down peptide bonds of a protein molecule) improved the BW, feed efficiency and carcass performances of broilers than the performances of animals consumed the diets without any papain. Additionally, there was a main effect of protease on FCR with birds fed diets with protease having a lower FCR than those without (Vieira et al, 2013;walk et al, 2018 had a positive effect on broiler performance and feed efficiency.…”
Section: Growth Performancementioning
confidence: 93%
See 1 more Smart Citation
“…Similar to these previous studies, our findings showed that dietary supplementation of acid protease in corn-soybean meal-based diets linearly increased BWG and decreased the FCR during 18 to 35 days and overall. Rumokoy et al, (2016) also demonstrated that all treatment level (0.03, 0.05 and 0.07%) of papain crude extract (a proteolytic enzyme that can break down peptide bonds of a protein molecule) improved the BW, feed efficiency and carcass performances of broilers than the performances of animals consumed the diets without any papain. Additionally, there was a main effect of protease on FCR with birds fed diets with protease having a lower FCR than those without (Vieira et al, 2013;walk et al, 2018 had a positive effect on broiler performance and feed efficiency.…”
Section: Growth Performancementioning
confidence: 93%
“…growth (Aureli, Kluenter, Fru, & Umar, 2011;Dosković et al, 2013;Kobayashi, Murai, Okada, & Okumura, 2002;Naveed, Acamovic, & Bedford, 1999;Oxenboll, Pontoppidan, & Frunji, 2011;Rumokoy, Pudjihastuti, Untu, & Toar, 2016;Selim et al, 2016).…”
mentioning
confidence: 99%